Impact of Investment Openness on National External Wealth: Based on Valuation Effects Perspective - Kun Liu; Lingchen Lu; Jianwei Xu (Discrete Dynamics in Nature and Society)
In recent years, the rise of investment protectionism has led to the decline of investment openness all over the world. Based on the perspective of valuation effects which affects changes in national external wealth, we carry out empirical analysis and find that investment openness has inhibitory effect on national external wealth in the short term but promotes it in the lag period. Furthermore, we use the open economy macroeconomic theory (NOEM) to construct DSGE model and find that reducing the degree of investment openness will lead to the rise of domestic investment asset prices and produce positive valuation effects, which will lead to the short term increase of national external wealth. However, this effect has poor persistence. In the long run, the reduction of openness will hinder transnational investment, reduce the income of transnational investment, and eventually lead to the deterioration of national external wealth. The DSGE model we constructed can be applicable for solving some problems for open economic policy. From the conclusion we have acquired, it is indicated that nations who want to maintain the steady growth of the external wealth should continue to improve investment openness and international investment environment, alleviate investment information asymmetry, and avert increasing investment protectionism.